Respon Produksi Rumput Gajah (Pennisetum Purpureum), Benggala (Panicum Maximum) dan Setaria (Setaria Spacelata) terhadap Perbedaan Salinitas - Diana sawen; Merlyn N. Lekitoo; Martha Kayadoe; Onesimus Yoku; M. Djunaedi (Jurnal Riset Agribisnis dan Peternakan, 2020)
Forage is a ruminant animal basal feed, where sufficient and continuous availability and good quality must be a priority. Place to growth or location, also determine the existence and production of forage including grass species in this study. This study aims to determine how much the production of elephant grass, panicum and cetaria on salinity differences. The study was conducted for 4 months, in Kompleks Perumahan dosen UNIPA Amban in Manokwari West Papua. The study was designed with a split plot design in to Completely Randomize design (CRD) 4x3 with 4 replications. As the main plot is grass species and the subplot is salinity based on growing media. Factor I is grass species (Sp) consisting of: Pennisetum purpureum (Sp1), Panicum maximum (Sp2) and Setaria spacelata (Sp3) and then Factor II is growing media (M) consisting of: soil 100% (M0), soil 70% + 30% of sand (M1), soil 50% + 50% of sand (M2) and soil 30% + 70% of sand (M3). Statistical analysis shows that the effect of salinity is significant (P<0.05) on plant growth variable, namely fresh matter production, dry matter production and stem leaf ratio. Planting media M1 (soil 70% + sand 30%) perform the best result, and species that is responsive to salinity is Panicum maximum (Sp2).